Age estimation by palatal suture using modified Kamijo’s method - Kobayashi, Susumu; Makino, Yohsuke; Torimitsu, Suguru; Mizuno, Satomi; Yamaguchi, Rutsuko; Chiba, Fumiko; Tsuneya, Shigeki; Iwase, Hirotaro (Forensic science international, 2023)
The present study aimed to investigate the correlation between palatal suture obliteration and age in modern Japanese and to develop an age estimation equation by modifying Kamijo's (1949) method. The subjects were 195 Japanese skeletal remains (155 males and 40 females) whose age and sex were known. First, obliteration score (OS) was obtained by measuring palatal suture obliteration from photographic images taken at the time of forensic autopsy, and the correlation with age was examined; no significant correlation was found in females. Second, the palatal sutures were divided into 14 sections, and each section was scored from 0 to 4 points according to the degree of the suture obliteration. Suture scores (SS) were then calculated for each of the four sutures, and the sum of the 14 scores (TSS: total suture score) was used to perform regression analysis for age. For male and all subjects (male and female), age significantly increased (p < 0.001) according to increment of SSs for all sutures. TSS has the highest regression coefficient (r = 0.540), and the lowest standard error of estimation (13.54 years) for all of the patients. The intra- and inter-observer agreement scoring showed high reliability. Validation study using the formulae showed a high percentage of correct responses (80 %). In conclusion, age estimation regression formula by palatal suture using modified Kamijo’s method was established for Japanese population, and the study showed the formula might be valid for age estimation. •Scoring the degree of fusion of palatal sutures improves the accuracy of the age estimation method.•In females, the sample size was small and there was no significant correlation between palatal suture obliteration and age.•Scoring the degree of fusion of palatal sutures correlated with age in females as well.•The simple regression equation obtained in this study may help in establishing the age of unidentified skeletal remains.